PEMBUATAN ARCADE GAME “GUESS THE ALPHABET!” BERBASIS ANDROID - Linda Sari; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
Game “Guess The Alphabets!” is designed using Unity and C# Sharp for the game’s script. This game has 2 Modes, namely Monster Mode and Learn Monster Mode. Monster Mode is a Mode where players are asked to guess the letters that are on the body of a Monster. Learn Monster Mode is a Mode where players are asked to type the English words. The player must complete the first stage in Monster Mode then proceed to the easy stage in Learn Monster Mode. And so on until the last stage in Monster Mode and Learn Monster Mode. Monster Mode consists of 4 stages. Each stage in Monster Mode consists of 5 levels. Learn Monster Mode consists of 4 stages, namely easy, normal, hard, and extreme stages. Testing is done by this method blackbox testing, alpha testing, and beta testing through a survey of 31 respondents. Test results show that the game “Guess The Alphabet!” is an interesting and challenging game because the players keep trying until it's finish the game.